2014
DOI: 10.1242/dev.102020
|View full text |Cite
|
Sign up to set email alerts
|

Forward and feedback regulation of cyclic steroid production in Drosophila melanogaster

Abstract: In most animals, steroid hormones are crucial regulators of physiology and developmental life transitions. Steroid synthesis depends on extrinsic parameters and autoregulatory processes to fine-tune the dynamics of hormone production. In Drosophila, transient increases of the steroid prohormone ecdysone, produced at each larval stage, are necessary to trigger moulting and metamorphosis. Binding of the active ecdysone (20-hydroxyecdysone) to its receptor (EcR) is followed by the sequential expression of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 57 publications
(78 reference statements)
2
45
1
Order By: Relevance
“…In D . melanogaster , Dm E75B binds to Dm HR3 (Reinking et al ., ; Palanker et al ., ) in a NO‐dependent manner (Cáceres et al ., ) to regulate ecdysteroidogenesis (Parvy et al ., ). The expression profiles suggest the conserved functions in ecdysteroidogenesis regulation of the three LdE75 s in L. decemlineata .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In D . melanogaster , Dm E75B binds to Dm HR3 (Reinking et al ., ; Palanker et al ., ) in a NO‐dependent manner (Cáceres et al ., ) to regulate ecdysteroidogenesis (Parvy et al ., ). The expression profiles suggest the conserved functions in ecdysteroidogenesis regulation of the three LdE75 s in L. decemlineata .…”
Section: Discussionmentioning
confidence: 97%
“…In D . melanogaster , feeding 20E rescued a developmental defect in E75 RNAi larvae (Parvy et al ., ). All of these results demonstrate that E75 knockdown leads to 20E deficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is essential for larval development, responding to ecdysone regulatory pathways at the onset of metamorphosis [19]. E75 is required for ecdysteroid biosynthesis in the prothoracic gland, and it counteracts DHR3 to avoid the premature repression of steroidogenesis [20]. Germline clones of E75 mutations cause germline arrest prior to meiosis entry, and degeneration of oocytes with follicle cell migration defects [21,22].…”
Section: E75/nhr-85/rev-erb (Nr1d)mentioning
confidence: 99%
“…More recently, it was shown that EcR-dependent positive feedback operating downstream of PTTH signaling plays a critical role in generating the high-level pulse that triggers pupariation in response to PTTH (Moeller et al, 2013). Complex interaction among the NRs, EcR, E75, DHR3, and bFTZ-F1, which mediate ecdysone signaling (King-Jones and Thummel, 2005), appears to be involved in regulating ecdysteroidogenesis (Parvy et al, 2014). Although those studies clearly indicated the involvement of the NRs in regulating ecdysteroidogenesis, the link from PTTH signaling to the NRs is not very clear.…”
Section: Introductionmentioning
confidence: 99%